Subthreshold defect formation in YBa 2Cu 3 O7-δ at nonuniform heating of electron gas in electromagnetic field - Adokin, V. T.; Gorelov, B. M.; Ogenko, V. M.; Melnikov, V. S.; Kevdina, I. B.; Shalyapina, G. M. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2002)
In YBa2Cu3O7-δ high temperature superconductors with δ<0.3 the irradiation by super high-frequency electromagnetic field with impulse power 104-106 W gives rise to a decrease of the rates of annihilation and capture of positrons, a growth of resistance, residual resistance, thermopower and the block of diffusive transitions of Au atoms, which are caused by the subthreshold defect formation in the intermediate layers. The irradiation effect is enhanced with rise of the number of defects in samples and does not depend on an impulse power. The defect formation is related to the excitation of low-frequency weakly damped collective excitations under irradiation, whose propagation through the crystal is accompanied by the Coulomb ejection of atoms from the lattice sites and the transformation and transport of defects.